Histopathological evaluation of minor salivary gland papillary–cystic tumours: focus on genetic alterations in sialadenoma papilliferum and intraductal papillary mucinous neoplasm. Issue 3 (1st December 2019) - Nakaguro, Masato; Urano, Makoto; Ogawa, Ikuko; Hirai, Hideaki; Yamamoto, Yoshinari; Yamaguchi, Hiroshi; Tanigawa, Maki; Matsubayashi, Jun; Hirano, Hiroshi; Shibahara, Junji; Tada, Yuichiro; Tsuzuki, Toyonori; et al.
Abstract : Aims: Minor salivary gland tumours showing a predominant papillary–cystic structure are rare, and constitute a mixture of various types of neoplasm; thus, the histopathological assessment of these tumours poses a significant diagnostic challenge. We aimed to delineate the histological characteristics of these tumours and further mutational aspects with a particular focus on sialadenoma papilliferum (SP) and intraductal papillary mucinous neoplasm (IPMN). Methods and results: We retrieved 28 papillary–cystic tumours of the minor salivary glands, and performed histological re‐evaluation and mutation analyses of several key oncogenes. The histological classifications were as follows: SP ( n = 10), SP‐like intraductal papillary tumour (SP‐IPT) ( n = 2), IPMN ( n = 9), intraductal papilloma, cystadenoma, and cystadenocarcinoma (two, three and two respectively). Whereas SP typically consisted of a combination of exophytic squamous epithelium and endophytic intraductal papillary infoldings, SP‐IPT lacked the exophytic component. SP and SP‐IPT frequently harboured BRAF V600E mutations (75.0%), which were identified in both squamous and ductal components. IPMN was characterised by a well‐demarcated cystic lesion filled exclusively with a papillary proliferation of mucinous cells and a high rate of AKT1 E17K mutations (88.9%). Intraductal papillomas were unilocular cystic lesions with intraluminal papillary growth of bland columnar cells. In contrast, both cystadenomas and cystadenocarcinomas showed a multicystic appearance with a papillary configuration. Cystadenocarcinomas invaded the surrounding tissue and were composed of markedly atypical tumour cells. Conclusion: The appropriate interpretation of histological findings and specific genetic alterations (e.g. BRAF V600E and AKT1 E17K in SP and IPMN) would be useful for the correct diagnosis of minor salivary gland papillary–cystic tumours.